Landscape Master Plans in University Campuses - Sefer Çon; Zöhre Polat (Turkish Journal of Agriculture: Food Science and Technology)
The concept of the university campus and research, taken up the development process of the universities, presented examples from the world and Turkey. Master plans, sustainable master plans and landscape master plans in university campuses were compiled and supported with examples. According to the survey, which examined 20 universities in 16 of the world where the campus master plan, which examined 20 universities in Turkey 12 patients which were put forward in the campus master plan. World in 7 of 10 universities surveyed across the campus landscape master plan that, while Turkey’s 10 universities discussed in general only 2 of the campus landscape master plan was put out to be. Suggestions regarding the necessity of preparing master plan and landscape master plan in university campuses are presented.